THE EFFECT OF PEOPLE, PHYSICAL EVIDENCE, PROCESS AND PRICE FAIRNESS ON PATIENT SATISFACTION AND REVISIT INTENTION AT THE XYZ HOSPITAL POLYCLINIC, MAKASSAR CITY - Vena Angelica; Innocentius Bernarto (FEB Universitas Sam Ratulangi Manado, 2023)
Abstract This study aims to determine the factors of patient satisfaction and the effect on revisit intention. The factors are people, physical evidence, process and price fairness. A written questionnaire is used in collecting respondent data. Total respondents obtained were 277 people. Convenience sampling method is used as a sampling method. The collected data were analyzed using PLS-SEM with SmartPLS software. The research results obtained are people, physical evidence and price fairness that have a positive effect on patient satisfaction. However, for the process variable it was found to have no positive effect on patient satisfaction. Patient satisfaction has a positive effect on revisit intention. The people factor is the most influential factor on patient satisfaction. Abstrak Penelitian ini bertujuan untuk mengetahui faktor kepuasan pasien dan pengaruhnya terhadap niat berkunjung kembali. Faktor tersebut adalah manusia, bukti fisik, proses dan keadilan harga. Kuesioner tertulis digunakan dalam mengumpulkan data responden. Total responden yang diperoleh adalah 277 orang. Metode convenience sampling digunakan sebagai metode pengambilan sampel. Data yang terkumpul dianalisis menggunakan PLS-SEM dengan perangkat lunak SmartPLS. Hasil penelitian yang diperoleh adalah people, physical evidence dan price fairness yang berpengaruh positif terhadap kepuasan pasien. Namun untuk variabel proses ditemukan tidak berpengaruh positif terhadap kepuasan pasien. Kepuasan pasien berpengaruh positif terhadap niat berkunjung kembali. Faktor people merupakan faktor yang paling berpengaruh terhadap kepuasan pasien